Non-HLA Antibodies in Kidney Transplantation: Pathogenesis, Clinical Impact, and Management Approaches - Vikash Chandra Mishra; Dinesh Chandra; Vimarsh Raina (Transplantology)
Antibody-mediated rejection is a critical factor in acute and chronic allograft rejection, with Human Leukocyte Antigen as the primary target of the humoral immune response in kidney transplants. In addition to HLA antibodies, non-HLA Abs also play a significant role in AMR. These non-HLA Abs, which can target either autoantigens or alloantigens, may be present pre-transplantation or develop post-transplant. They are associated with various types of allograft injury. The major non-HLA Abs include those directed against the angiotensin II type 1 receptor, endothelin type A receptor, and MICA, as well as other antigens such as vimentin, collagens, and anti-endothelial cell antibodies. Factors such as ischemia, reperfusion injury, and calcineurin inhibitor toxicity can trigger the pathogenic activity of these Abs. The mechanisms underlying non-HLA Ab production are not yet fully understood but are thought to involve endothelial injury and the exposure of neoantigens. Research indicates that these non-HLA Abs can cause graft injury through both complement-dependent and complement-independent pathways. However, detecting non-HLA Abs remains a challenge due to the lack of reliable diagnostic tools. Current treatment strategies for managing the effects of pathogenic non-HLA Abs include intravenous immunoglobulin, plasmapheresis, rituximab, and bortezomib. Early identification of high-risk patients and timely intervention are crucial to preventing graft failure. This review examines the development, mechanisms, and clinical significance of non-HLA Abs in kidney transplantation, highlighting the need for improved diagnostic methods and tailored therapeutic approaches.